Persistent Hypercalcemia Crisis and Recurrent Acute Pancreatitis Due to Multiple Ectopic Parathyroid Carcinomas: Case Report and Literature Review of Mediastinal Parathyroid Carcinoma - Jiajue, Ruizhi; Song, An; Wang, Ou; Li, Wei (Frontiers in Endocrinology, 2020)
Mediastinal parathyroid carcinoma (PC) is a very rare entity in primary hyperparathyroidism. The aim of this report is to illustrate a case of mediastinal PC, and to provide a systemic literature review of this rare condition. A 34-year-old woman who had already underwent two cervical operations for hyperparathyroidism suffered a recurrence, presenting with recurrent acute pancreatitis and persistent parathyroid crisis. Combined Technetium-99 methoxyisobutylisonitrile imaging (MIBI) and computed tomography scanning (CT) confirmed 3 parathyroid tumors, one was the recurrence of residual tumor locating in the thyroid region, and the other two were ectopic tumors respectively locating in the suprasternal fossa and in the thymus region. Pathological finding confirmed the diagnosis of multiple ectopic PCs. She experienced hungry bone syndrome postoperatively, and was treated with large oral doses of calcium carbonate and calcitriol. The literature review was run by searching PubMed MEDLINE from 1951 to 2019 for studies of all types in the English language only, using the terms “mediastinal, mediastinum, parathyroid, carcinoma”. Including our reported case, a total of 26 cases with ectopic mediastinal PCs were assessed for demographic data, tumor location and size, biochemical findings, and symptomatology, etc. 65.4% of patients were men, with mean age of 46 years, mean serum calcium of 14.6mg/dl, and mean serum intact parathyroid hormone of 1764pg/ml. 95.8% of carcinomas located in the anterosuperior mediastinum, and 4.2% in the middle mediastinum, with mean diameter of 49.3mm, and mean weight of 186.8g. MIBI and CT were the most commonly used methods to localize these mediastinal tumors, with 73.3% and 100% positivity respectively. Over half patient experienced more than one operation. Diagnosis and treatment of mediastinal PCs represent a challenge. Early suspicion, appropriate preoperative localization studies, and the cooperation of endocrinologists and surgeons are the key issues in effective management.